Strategi Pendekatan Bawaslu dalam Merespon Krisis Kepercayaan Publik di Kecamatan Bantimurung - Ros, Rosmiati Anas; Najamuddin, Najamuddin; A. Octamaya Tenri Awaru; Darman Manda; Idham Irwansyah Idrus (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2025)
This article will discuss the strategies used by the Election Supervisory Agency (Bawaslu) in responding to the crisis of public trust in the Bantimurung District. This research employs a qualitative method with a case study approach. Data collection techniques involve in-depth interviews, field observations, and the study of relevant documents regarding Bawaslu's work program. Research informants consist of the Chairperson and members of Bawaslu, community leaders, political party officials, and the general public. The research findings indicate that Bawaslu's main strategies include increasing information transparency through mass media broadcasts and periodic meetings with stakeholders; optimizing the supervision functions to prevent money politics and campaign violations at the sub-district/village level; improving public complaint services; and massive socialization of Bawaslu's roles and functions to schools, community organizations, and the general public. However, the implementation of these strategies is still not fully effective due to obstacles such as human resources, budget constraints, inter-agency coordination, and lack of regulatory support. The conclusion of this research is that strong commitment and collaboration are needed from various stakeholders, including local governments and regional representative councils (DPRD), to support efforts to restore public trust in Bawaslu in the Bantimurung District.